Structural Characterization of the RNA-Binding Protein SERBP1 Reveals Intrinsic Disorder and Atypical RNA Binding Modes - Baudin, Antoine; Moreno-Romero, Alma K.; Xu, Xiaoping; Selig, Emily E.; Penalva, Luiz O. F.; Libich, David S. (Frontiers in Molecular Biosciences, 2021)
RNA binding proteins (RBPs) are essential for critical biological processes such as translation regulation and mRNA processing, and misfunctions of these proteins are associated with diseases such as cancer and neurodegeneration. SERBP1 (SERPINE1 mRNA Binding Protein 1) is an RBP that comprises two RG/RGG repeat regions yet lacks other recognizable RNA-binding motifs. It is involved in mRNA maturation, and translational regulation. It was initially identified as a hyaluronic acid binding protein, but recent studies have identified central roles for SERBP1 in brain function and development, especially neurogenesis and synaptogenesis. SERBP1 regulates One-carbon metabolism and epigenetic modification of histones, and increased SERBP1 expression in cancers such as leukemia, ovarian, prostate, liver and glioblastoma is correlated with poor patient outcomes. Despite these important regulatory roles for SERBP1, little is known about its structural and dynamic properties, nor about the molecular mechanisms governing its interaction with mRNA. Here, we define SERBP1 as an intrinsically disordered protein, containing highly conserved elements that were shown to be functionally important. The RNA binding activity of SERBP1 was explored using solution NMR and other biophysical techniques. The outcome of these experiments revealed that SERBP1 preferentially samples compact conformations including a central, stable α-helix and show that SERBP1 recognizes G-rich RNA sequences at the C-terminus involving the RGG box and neighboring residues. Despite the role in RNA recognition, the RGG boxes do not seem to stabilize the central helix and the central helix does not participate in RNA binding. Further, SERBP1 undergoes liquid-liquid phase separation, mediated by salt and RNA, and both RGG boxes are necessary for the efficient formation of condensed phases. Together, these results provide a foundation for understanding the molecular mechanisms of SERBP1 functions in physiological and pathological processes.